Superacid-Mediated Intramolecular Cyclization/Condensation: Facile One-Pot Synthesis of Spirotetracyclic Indanones and Indenes - Ramulu, Bokka Venkat; Kumar, Devarapalli Ravi; Satyanarayana, Gedu (Synlett, 2017)
A facile, superacid-promoted, domino, one-pot synthesis of novel spirotetracyclic indanones through intramolecular Friedel–Crafts acylation/alkylation of α,β-unsaturated cinnamic acid esters is presented. Interestingly, when the β-aryl group contained electron-withdrawing substituents such as fluoro, chloro, or bromo, the reaction took a different mechanistic path and afforded arylindenes as the end products.
Keywords: superacids; Friedel–Craft reaction; spiro compounds; indanones; indenes; domino reactions